(untitled) (The Review of Diabetic Studies, 2024)
Nursing care for patients with Gastroesophageal Reflux Disease (GERD) is a comprehensive, patient-centered process that integrates clinical expertise with holistic support to manage this chronic condition effectively. The nurse’s role is multifaceted, encompassing thorough patient assessment to identify classic and atypical symptoms, detailed education on pathophysiology and the importance of treatment adherence, and skilled coaching on evidence-based lifestyle and dietary modifications. Nurses provide critical support in pharmacological management, ensuring patients understand the proper use of acid-suppressive medications like proton pump inhibitors, and they offer essential psychological support to address the anxiety and reduced quality of life associated with chronic symptoms. Furthermore, they play a key collaborative role in diagnostic procedures and provide specialized pre- and post-operative care for patients undergoing anti-reflux surgery. Through continuous monitoring, evaluation, and empowerment, nurses enable patients to achieve optimal symptom control, prevent complications, and improve their overall well-being, demonstrating the indispensable value of the nursing discipline in the long-term, interdisciplinary management of GERD.